Intellectual Games: Stimulating the Development of The Human Mind - Shoira Kubayeva (Scientific Trends, 2023)
This article examines the role of intellectual games in stimulating the development of the human mind. Intellectual games are an effective way to develop intelligence, erudition and thinking. They require the use of mental abilities and promote the formation of concepts, analysis and synthesis of information. In addition, intellectual games contribute to the development of such qualities as resourcefulness, analytical ingenuity, humour and speed of memory. The article also discusses the features of the organization of intellectual and creative games in the educational process and their influence on the formation of skills and personal qualities of students.
Keywords: Intellectual games, development of the mind, thinking, erudition, resourcefulness, analytical ingenuity, educational process.